Exponential decay for a Klein–Gordon–Schrödinger system with locally distributed damping - Marilena Poulou; Michael Filippakis; Janaina Zanchetta (Electronic Journal of Qualitative Theory of Differential Equations)
A coupled damped Klein–Gordon–Schrödinger equations are considered where $Ω$ is a bounded domain of $\mathbb{R}^{2},$ with smooth boundary $Γ$ and $ω$ is a neighbourhood of $\partial Ω$ satisfying the geometric control condition. The aim of the paper is to prove the existence, uniqueness and uniform decay for the solutions.